Anthropological Aspect of Charles Sanders Peirce’s Metaphysical Cosmology - Volodymyr Melnyk; Andrii Synytsia (Философия и космология, 2021)
The article demonstrates how Charles Sanders Peirce built cosmological ideas based on the analysis of the specifics of a human being. It is proved that the possibility of a certain degree of anthropocentrism in Peirce’s cosmological conception was laid down in the categorical system, including the level of the Firstness, Secondness, and Thirdness. It is shown why according to his scientific metaphysics, for everyone, the concept that corresponds to human nature is more true than other ones, as well as why a person instinctively feels the truth. This situation is possible because the laws of thought are formulated in accordance with the laws of nature. Human nature reflects what is in the world. Thus, through self-knowledge, a person also discovers reality itself as a dynamic universe in which the physical and he mental, the real and the ideal are subject to the same laws (habits-regularities). However, human beings do not know all of them, but only those that correspond to the level of their understanding and interests. Subsequently, science and technology are built on the basis of individuals’ own intentions. Human beings realize that the universe is boundless and not everything they are able to understand and justify. This makes fallibilism inevitable. It is analyzed how to solve the difficulties of fallibilism; Peirce proposed to use the concept of practical certainty as a basic criterion for recognizing the system of knowledge about the world as true. It is shown that the concepts of tychism, synechism, and agapism, which reveal the meaning of Peirce’s cosmological theory of evolution, are also based on the principles of anthropocentrism and anthropomorphism. Thus, it is argued that human being becomes the key to understanding Peirce’s metaphysical cosmology.